2020
DOI: 10.1038/s41598-020-58493-7
|View full text |Cite
|
Sign up to set email alerts
|

VGLL3 is a prognostic biomarker and correlated with clinical pathologic features and immune infiltrates in stomach adenocarcinoma

Abstract: Due to its poor clinical outcome, there is an urgent need to identify novel prognostic markers for stomach adenocarcinoma (STAD). Here, we aimed to explore the relationship between VGLL3 expression and clinico-pathological features, dendritic cells, macrophages, and prognosis of STAD. VGLL3 expression levels were significantly associated with histological grade, T stage, and TNM stage. VGLL3 levels and patient's age were also independent prognostic factors of the clinical outcome of STAD. In addition, VGLL3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
(37 reference statements)
2
22
0
Order By: Relevance
“…The.gmt format data were obtained from the Molecular Signatures Database (MSigDB) using gene set enrichment analysis (GSEA) version 3.0. Furthermore, enrichment analysis was performed with a random combination number of 1000 and a false discovery rate (FDR) of 0.05 as criteria for significantly enriched genes ( 22 ). The gene sets were classified into Wnt2 high- and low-expression groups as based on the median Wnt2 expression level, and the effect of Wnt2 expression was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…The.gmt format data were obtained from the Molecular Signatures Database (MSigDB) using gene set enrichment analysis (GSEA) version 3.0. Furthermore, enrichment analysis was performed with a random combination number of 1000 and a false discovery rate (FDR) of 0.05 as criteria for significantly enriched genes ( 22 ). The gene sets were classified into Wnt2 high- and low-expression groups as based on the median Wnt2 expression level, and the effect of Wnt2 expression was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that SUPV3L1 and SLC22A17 affect immune cell infiltration, leading to the different prognosis of patients in gastric cancer [13]. In stomach adenocarcinoma, VGLL3 is identified as a novel prognostic biomarker and correlated with immune infiltrates [14]. However, the association between gene expression, the infiltration of immune cells, and prognosis has not been completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sarcoma, VGLL3 expression was found to be positively correlated with accelerated grade and poor prognosis in gastric tumor (26). VGLL3-high gastric tumor showed the activation of the MAPK, JAK-STAT, and WNT pathways together with enhanced immune infiltrates (57). These features in VGLL3-high tumors may reflect the proinflammatory functions of VGLL3 which were found in VGLL3-overexpressing mice (58).…”
Section: Vgll3 Is Involved In Both Tumor Development and Suppressionmentioning
confidence: 90%